Immunomodulatory Action of Parasympathetic Stimulation promoted by Physical Exercise (Fiep Bulletin - online, 2024)
Introduction: Physical exercise promotes the stimulation of the vagal nerve and different neural networks, contributing to a more effective anti-inflammatory response in order to contribute to cardiovascular, metabolic and immunological benefits. Objective: To associate the role of physical exercise with parasympathetic stimulation and its possible implications in immunomodulation Methods: This is a qualitative, explanatory and descriptive study on the immunomodulatory action of parasympathetic activation through physical exercise through a bibliographic review. The databases used were: PubMed, Scopus, Scielo and Web of Science involving all original articles from January 2015 and June 2024. Results: The main findings are related to differences in physical exercise intensity, which can contribute to the modulation of the innate immune system and the expression of neutrophil and lymphocyte cell populations, which can contribute to a more specific immune response. Aerobic training and strength training had similar responses in reducing BMI and glycated hemoglobin, reducing sympathetic tone, increasing parasympathetic tone, and improving the sympatho/vagal balance for controlling heart rate variability. There was a negative association between vagal neuroimmunomodulation (NIM) and mortality, since the lower the NIM index, the shorter the survival time in the population sample. Conclusion: Aerobic physical exercise and strength training can contribute to the activation of the parasympathetic system and immune system and provide better adjustments in the innate and adaptive immune response dependent on the intensity and volume of training.
Keywords: Physical Exercise; Parasympathetic Stimulation; Immune System; Vagus Nerve; Neuromodulation